PENDIDIKAN KARAKTER PADA LEMBAGA FORMAL: Dalam Perspektif Pendidikan Pesantren - Minhaji Minhaji; Hariyanto Hariyanto (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2015)
Ten destructions of a nation currently prevalent in Indonesia. Many bad examples has been shown by the elite leaders, student or always involved in negative habit like drugs, free sex, fights and other. If education is not able to answer their needs, surely Indonesian will get lose one generation. Character education in this study more emphasis on character education in perspective of Pesantren, where the uniqueness perceived from the outset has implemented character education. There are three issues related to character education in formal education, intellectual, prophetic character and internalization ESQ as habit.